Quantification of the metabolic and physical demands of the 90-second box jump - Gross, M.; Hoppeler, H.; Vogt, M. (Journal of Athletic Enhancement, 2014)
Introduction: The goal of the 90-second box jump (BJ90) is to perform as many lateral jumps as possible onto and off of a bench within 90 seconds. We aimed to determine the physiological and biomechanical demands of the BJ90.